PERAN KECERDASAN INTELEKTUAL DAN SELF REGULATED LEARNING TERHADAP PRESTASI BELAJAR MAHASISWA - Usman Hidayat (Psympathic : Jurnal Ilmiah Psikologi, 2011)
This research specifically observes the personal factors of students, both demo-graphically and psychologically expected to influence to achievement of study had by them. Demographic factor that will be observed is intellectual quotient and psychological factor that will be observed is self regulated learning. Self regulated learning comes from the concept of self regulation which is said by Bandura (1997), but it has been modified and specified for education domain by Zimmerman (2000). This research plan applies correlation plan, multiple regression. The research data include: (1) primer data, i.e., data correlating to self regulated learning, and (2) secondary data, i.e., the data correlating to the standard of quotient and the result of study achievement (IPK). The secondary data is gotten from the result of psycho test implemented by the laboratory of Sunan Gunung Djati Bandung State Islamic University psychology faculty and the data existing in Sunan Gunung Djati Bandung State Islamic University Psychology Faculty. The result of analysis data shows that the correlation coefficient of all three independent variables with dependent variable = 0.564 and R2 = 0.310. It shows that 31 percent of  study achievement variety is determined by intellectual quotient and self regulated learning. Furthermore, 69 percent of it is determined by the other variables.